Implementasi Sistem Informasi Tata Usahapada Sekolah Gemanurani - Dewi Ayu Puspitawati; Kresno Murti Prabowo; Farhan Afif Aldiansyah; Sabar Hanadwiputra (LPPM STMIK IKMI Cirebon, 2023)
The development of the information system for the Gemanurani Integrated Islamic School experienced obstacles because it was carried out based on the personal needs of the developer at that time. So that the development carried out is not necessarily appropriate or has optimal benefit values ​​in the future. Along the way, there have been many changes to forms, reports and system procedures. This shows that the development of the information system is not based on existing needs, so it is difficult for management to make decisions. The Gemanurani Integrated Islamic School started the development of Information Systems from New Student Admissions (PSB), Finance, Administration (TU), Study Programs (PRODI), Students and Teachers without Human Resources Development (HRD). One of the Operator's routine tasks is inputting school data where the application is still done manually using MS. Excel, problems often arise when calculating teacher valuations, teachers across school programs and employee deductions. By prioritizing the development of administrative information systems according to needs, it is hoped that it will make it easier for Operators in processing employee and teacher data. The goal is to facilitate schools in time management and data security.